2019
DOI: 10.3233/wor-192949
|View full text |Cite
|
Sign up to set email alerts
|

Work-related stress levels and musculoskeletal disorders among municipal solid waste collectors in Ankara

Abstract: BACKGROUND: Industrialization and rising standards of living have contributed to a growing amount of solid waste and consequent disposal problems. Solid waste collection is among the occupations with the highest risk for musculoskeletal disorders. OBJECTIVE:We have conducted this study to assess musculoskeletal complaints and work-related stress levels among municipal solid waste (MSW) collectors. METHODS:The subjects were all currently employed at the MSW Department of the City of Ankara, Turkey. Validated qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 25 publications
3
10
0
6
Order By: Relevance
“…However, 2854 HCWs belonging to the low-risk group complained of at least one evocative symptom, but only 0.52% of them were affected by COVID-19. Work-related stress seem to be widespread among medical practitioners and in other working settings ( De Sio et al, 2020 , Bulduk, 2019 , Eskildsen et al, 2017 , Li et al, 2016 ), it also has increased during the pandemic in COVID-19 hospitals ( Blake et al 2020 ); therefore it is possible to presume that the high prevalence of symptoms could be also linked to this mental condition. Work-related stress not only affects the physician's mental and physical well-being, but also patient care quality and the overall efficiency of the healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…However, 2854 HCWs belonging to the low-risk group complained of at least one evocative symptom, but only 0.52% of them were affected by COVID-19. Work-related stress seem to be widespread among medical practitioners and in other working settings ( De Sio et al, 2020 , Bulduk, 2019 , Eskildsen et al, 2017 , Li et al, 2016 ), it also has increased during the pandemic in COVID-19 hospitals ( Blake et al 2020 ); therefore it is possible to presume that the high prevalence of symptoms could be also linked to this mental condition. Work-related stress not only affects the physician's mental and physical well-being, but also patient care quality and the overall efficiency of the healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, only one study reported the prevalence of anxiety and depression among Japanese MSW incinerator workers, using the Japanese version of the Profile of Mood States Test [ 13 ]. Other studies investigated stressors [ 10 , 11 ] or the psychological work environment using the Job Content Questionnaires [ 4 , 12 ]. The higher prevalence of mental disorders in the Japanese study might be attributable to the study participants’ occupation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mean score (standard deviation) of DASS-S among WCs in this study was moderate (9.7 ± 7.8), 4.1% and 3.1% of WCs showed moderate to severe levels of stress symptoms, respectively. Research on psychological stress among WCs has thus far been limited [4,[10][11][12][13]. Among them, only one study reported the prevalence of anxiety and depression among Japanese MSW incinerator workers, using the Japanese version of the Profile of Mood States Test [13].…”
Section: Prevalence Of Psychological Stress Among Waste Collectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that 30% of European workers suffer from back pain, and the economic loss caused by back pain in Holland accounts for 1.7% of the national wealth every year. Furthermore [2,3], the number of days absent from work due to MSDs accounts for 15%-22% of the total as a consequence of industry-related diseases in the Federal Republic of Germany every year. The direct and indirect economic losses incurred in Canada due to MSDs are as high as nearly 100 billion US dollars every year.…”
Section: Introductionmentioning
confidence: 99%